2002
DOI: 10.1097/00000539-200206000-00051
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Comparison of Pulmonary Emboli Formation After Pneumatic Tourniquet Release in Patients Undergoing Reconstruction of Anterior Cruciate Ligament and Total Knee Arthroplasty

Abstract: We compared emboli formation after tourniquet release in patients undergoing arthroscopic reconstruction of the anterior cruciate ligament (ACL, n = 20) and total knee arthroplasty (TKA, n = 20) using transesophageal echocardiography. The present data suggest that the risk of acute pulmonary embolism after tourniquet release could be more frequent during TKA than ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Preoperative medications, pain, and use of opioids and other drugs postoperatively may as well affect cognitive status. Lastly, idiosyncrasies of the surgical procedure [59, 60], such as tourniquet use [60, 61, 62] reaming of the femur [42, 43] with potential for fat emboli, and cementing of the prosthesis [63], may influence the results. Tourniquet times were 21.0 (20.7) min.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative medications, pain, and use of opioids and other drugs postoperatively may as well affect cognitive status. Lastly, idiosyncrasies of the surgical procedure [59, 60], such as tourniquet use [60, 61, 62] reaming of the femur [42, 43] with potential for fat emboli, and cementing of the prosthesis [63], may influence the results. Tourniquet times were 21.0 (20.7) min.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a decrease in oxygen saturation 41,49,53 Increases in end‐tidal carbon dioxide occur 41,49,54–56 . The time for clearance of the metabolites depends upon the patient's physiologic status, extremity involved, and duration of tourniquet inflation. A decrease in core body temperature typically occurs upon deflation of a lower extremity tourniquet cuff 46,47,50 …”
Section: Purposementioning
confidence: 99%
“…While the tourniquet does not cause deep vein thrombosis, fatal pulmonary emboli have been reported at all stages of tourniquet use, from exsanguination to deflation (1,35,38) . Patients at high risk for deep vein thrombosis (DVT) and pulmonary embolism include those with lower limb trauma, prolonged immobilisation (greater than 3 days (2) ) or a history of DVT's (1) .…”
Section: Haematological Effectsmentioning
confidence: 99%
“…The embolus may consist of air, marrow contents, clot (38) or cement (37) . Venous embolism is more likely to occur when the marrow cavity is instrumented (35) , but avoidance of such manoeuvres does not prevent it (37) . The type of surgery may also influence the incidence of pulmonary embolism -Hirota et al (35) found an increased incidence of pulmonary emboli in total knee arthroplasties compared with anterior cruciate ligament reconstructions.…”
Section: Haematological Effectsmentioning
confidence: 99%
See 1 more Smart Citation